A pooling-LiNGAM algorithm for effective connectivity analysis of fMRI data - Xu, Lele; Fan, Tingting; Wu, Xia; Chen, KeWei; Guo, Xiaojuan; Zhang, Jiacai; Yao, Li (Frontiers in Computational Neuroscience, 2014)
The Independent Component Analysis - linear non-Gaussian acyclic model (LiNGAM), an algorithm that can be used to estimate the causal relationship among non-Gaussian distributed data, has the potential value to detect the effective connectivity of human brain areas. Under the assumptions that (a): the data generating process is linear, (b) there are no unobserved confounders, and (c) data have non-Gaussian distributions, LiNGAM can be used to discover the complete causal structure of data. Previous studies reveal that the algorithm could perform well when the data points being analyzed is relatively long. However, there are too few data points in most neuroimaging recordings, especially functional magnetic resonance imaging (fMRI), to allow the algorithm to converge. Smith’s study speculates a method by pooling data points across subjects may be useful to address this issue (Smith et al., 2011). Thus this study focus on validating Smith’s proposal of pooling data points across subjects for the use of LiNGAM, and this method is named as pooling-LiNGAM (pLiNGAM). Using both simulated and real fMRI data, our current study demonstrates the feasibility and efficiency of the pLiNGAM on the effective connectivity estimation.